Detecting Infectious Bursal Disease Using a VP1 Gene-Based RT-qPCR Assay Compared to Standard Methods of Virus Isolation, ELISA, and Histopathology - Okino, Cintia H. (2020)
Infectious bursal disease (IBD) is an immunosuppressive viral disease of chickens, associated with severe economic losses and major threats to poultry production worldwide. Disease prevention programs rely on unequivocal identification of the pathogen, as well as vaccination programs. This study developed a sensitive, one-step, real-time, quantitative reverse transcription polymerase chain reaction (RT-qPCR) assay using a hydrolysis probe system for infectious bursal disease virus (IBDV, VP1 gene) detection and quantification, which was compared to other routinely used diagnostic methods. The assay successfully detected IBD reference viruses and field isolates. The absence of cross-reactivity was detected with negative samples or with other avian viruses in the analytical specificity test. The detection limit of this assay was 70 RNA copies. RT-qPCR was more sensitive in the detection of serially diluted IBDV isolates compared to virus isolation. For clinical samples, the sensitivity and specificity values of RT-qPCR compared to enzyme-linked immunosorbent assay (ELISA) were 97.5% and 100%, respectively, and compared to histopathology, these values were 100% and 93.94%, respectively. RT-qPCR can provide a simple and reliable assay for IBDV surveillance programs and for evaluation of control strategies.